Mutations and Antimutagens in Emergency Medicine - V. V. Moroz; S. G. Smirnova; O. V. Ivanova; G. G. Poroshenko (Общая реаниматология)
Among other negative sequels, hypoxia that is the leading cause of all critical conditions increases the frequency of cell mutations in the patient. Unfortunately, we do not know whether there are available special studies analyzing the frequency of mutations in the germ cells of experimental animals or humans. But those in the somatic cells were reported in various publications more than 30 years ago. Specifically, such phenomena have been described in acute lung injuries and myocardial infarction in both rats and man. But these studies have been sporadic. And the increase in the frequency of somatic mutation affects the incidence of apoptosis, the change in the pattern of immunological processes and, possibly, even the factors of carcinogenesis. Mutagenetic processes can be managed, by modifying their frequency with antimuta-gens.